A Case of Live Birth after Uterine Reconstruction for Recurrent Cornual Ectopic Pregnancy following IVF Treatment - Deivanayagam Maruthini; Vinay Sharma (Case Reports in Obstetrics and Gynecology)
We present a case of recurrent ruptured right cornual ectopic pregnancies conceived after IVF. Following the second episode, a sonohysterography was undertaken to identify possible areas of scar weakness that may rupture with uterine distension in a future pregnancy. The scan revealed asymmetrical muscle thickness in the cornual regions, the right (6 mm) being thinner than the left (1.6 cm). Subsequently, an elective laparotomy was undertaken, and the cornua were reconstructed and thickened in several layers by bringing the laterally retracted myometrial fibres onto the reconstruction site. A sono-hysterography after surgery showed satisfactory (3-4 cm) myometrial thickness all around. A further cycle of IVF resulted in a singleton pregnancy. Pelvic scans confirmed normal intrauterine pregnancy without any myometrial thinning. She was delivered by an uneventful elective caesarean section at term. We propose that, in those who intend to have further pregnancies after a cornual ectopic pregnancy, a sono-hysterography is possibly the best investigative tool to assess myometrial integrity. This case demonstrates that in women with areas of muscle weakness it is possible to successfully perform an interval elective reconstructive surgery on the uterus that can result in an uneventful pregnancy and birth.